THE ANALYSIS OF THE STRATEGY OF FUNDRAISING AT THE INSTITUTE AMIL ZAKAT INFAQ AND SADAQAH MUHAMMADIYAH (LAZISMU) KABUPATEN SAMBAS - Minhani Minhani; Munadi Munadi; Ahmad Zabidi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
This study departs the activity of the fundraising done by Lazismu Kabupaten Sambas in carrying out the strategy of fundraising. Given the importance of the strategy is done, so Lazismu Kabupaten Sambas can further enhance its role in addressing the problem of poverty, then this research is very important to be researched more deeply. This study aims to determine and describe the formulation of the strategy fundraising Zakat, Infaq and Sadaqah in Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah Kabupaten Sambas.To understand and describe the factors supporting and inhibiting the implementation of the strategy fundraising Zakat, Infaq and Sadaqah in Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah Kabupaten Sambas. As for the focus issues used as a reference are as follows: How strategy formulation fundraising Zakat, Infaq and Sadaqah Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah di Kabupaten Sambas? How the factors supporting and inhibiting the strategy of fundraising zakat, infaq and Sadaqah Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah Kabupaten Sambas?. The approach in this study using a qualitative approach to the type of descriptive research. Research will be done is in the Amil Zakat Infaq and Sadaqah Muhammadiyah (LAZISMU) located in the high School of Muhammadiyah Sambas. The object of the study the researchers chose is about the strategy of fundraising in the amil zakat infaq and sadaqah Muhammadiyah. Strategy formulation fundraising Zakat, Infaq and Sadaqah Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah di Kabupaten Sambas through some of that: the Program of the Tube Infaq, Program Transfer ZIS. Factors supporting donors remains that of Muhammadiyah itself, the Population in the District of Sambas most of the population is majority Muslim, zakat management Institutions in the District of Sambas is still relatively little. As for the inhibiting factors of strategy fundraising zakat, infaq and Sadaqah Lembaga Amil Zakat Infaq and Sadaqah Muhammadiyah Kabupaten Sambas, among others: the Limitations of the human resources (HR) there is on the institutions, the limited facilities and infrastructure, the Limited available funds and funding to achieve not up to the target, a Way to retain the confidence of the donors who have contributed in the distribution of funds to the institution.